Assessment processes and principles related to Food Security that Zimbabwe can rely on for insight. (International Journal of Scientific Research and Management (IJSRM), 2021)
Increasing frequency and intensity of food insecurity in Zimbabwe, amidst heavy investment in Disaster Risk Reduction efforts threaten the achievement of the Zero Hunger target by 2030. The need to interrogate assessment practice need not be overemphasized. An interpretive–constructivist paradigm guided this study, while desktop review, focus group discussions and individual interviews were the main data collection tools. A purposively selected sample, of 85participants from Bulilima, Gwanda, Mangwe, and Umzingwane districts was used. These districts share similar social and cultural characteristics and hazards. The sample consisted of District development coordinators (DDCs), Environmental Management Agency, Rural District Council (RDC) chief executive officers, councillors, traditional leaders (chiefs), NGO managers, and heads of schools, deemed to bring depth into the study. NVivo software was used in data analysis to establish order, structure, and meaning, to ensure coherence, consistency, and quality of research findings and deductions. The study found that the term, “assessment” was variedly understood across disciplines and levels of responsibility, due to the existence of parallel assessment regimes that fragment and weaken assessment practice. Hence, the need to make capacity-building, training and education and stakeholder participation a permanent feature in Zimbabwe. This will promote correct understanding and application of the terms, and increase the knowledge of DRR practice. Assessment practice challenges emanate from the manner in which stakeholders do assessments. Hence, the need for attitude change and commitment to the pooling of all the resources towards the assessment practice, and adherence to standards and principles that govern assessment.